Oxford Readings in Ancient Literary Criticism - Laird, Andrew, Dr (Oxford readings in classical studies., 2006)
The literary criticism of classical Greece and Rome has had an extensive influence on modern thought. The important ancient critics discussed in this book include Plato, Aristotle and Horace. This volume has a helpful introduction, chronology and suggestions for further reading. It will appeal to any readers with interests in literature, criticism or aesthetics. All Latin and Greek quotations are translated. - ;The volume makes widely available some important scholarship on the canonical texts of ancient rhetoric and poetics. Whilst there are numerous studies of general trends in classical cri.